Estat?sticas de ordem superior para a distribui??o K-? - Duque, Renan Ralpe Sthel (2003)
In this dissertation the development of the second-order statistics for the K-? distribution was performed. The K-? distribution is a general approach to signal propagation in nonhomogeneous media and encompasses the Rayleigh, Rice and Nakagami-m distributions as special cases. As an original contribution we have the development of the equation of the rate of crossing of level and mean time of fading, the implementation of a simulator to generate a signal with fading K-? considering the Doppler effect for any value of K and my multiple of 1/2, the realization that the derivative of the envelope of a signal with fading K-? has a Gaussian distribution.